Futility-caveat lector - Graham R. Howarth (South African Family Practice, 2003)
In some ways, those persons who practise medicine have become of its victims. We wish to do the best for our patients. However, occasionally the advantages of the treatment may be marginal. Added to this is the spiraling cost of the medical therapy, something that doctors are aware of. To make the problem even more difficult, we have increasing awareness by patients and their families of the concepts of autonomy and patient's rights. They feel that they can demand treatment that the doctor may feel is of no or marginal benefit; possibly also at great expense. This card in these situations, that can usurp patient autonomy, in the sense that we do not have to give treatment that we consider to be futile, despite the patient requesting the treatment.